Analisis perhitungan dan pelaporan Pajak Pertambahan Nilai atas subsidi LPG berdasarkan PMK Nomor 11 tahun 2025 pada agen gas LPG 3 kg PT Fortuna Inti Gas di Kabupaten Minahasa Selatan - Keintjem, Given Pieter; Sabijono, Harijanto; Kapojos, Peter M. (Manajemen Bisnis dan Keuangan Korporat, 2025)
This study aims to explore how PT Fortuna Inti Gas calculates and reports Value Added Tax (VAT) on the sale of subsidized 3-kg LPG in accordance with the provisions of Minister of Finance Regulation (PMK) No. 11 of 2025. It also examines the challenges faced by the company and the strategies implemented to ensure tax compliance. The research uses a descriptive qualitative method, with data collected through interviews, observations, and document analysis. The findings show that the company calculates VAT based on the difference between the agent's selling price and the purchase price from Pertamina, using a tax rate of 1.1/101,1. Reporting is carried out monthly through the e-Faktur system. However, the company faces several obstacles, including limited human resources familiar with the updated regulations, technical issues with the reporting system, and a lack of internal data synchronization. To overcome these issues, PT Fortuna Inti Gas applies several strategies, such as internal training, the development of standard operating procedures for tax reporting, and collaboration with tax consultants. The results highlight the importance of regulatory understanding and administrative readiness in ensuring proper and sustainable tax compliance.